Exposure and Health Risk Assessment of Aflatoxin M1 in Raw Milk and Cottage Cheese in Adults in Ethiopia - Haftom Zebib; Dawit Abate; Ashagrie Zewdu Woldegiorgis (Foods, 2023)
Aflatoxin M1 (milk toxin) found in milk is formed from the hepatic biotransformation of AFB1 (aflatoxin B1) and poses a risk to human health when consumed. The risk assessment of AFM1 exposure due to milk consumption is a valuable way to assess health risk. The objective of the present work was to determine an exposure and risk assessment of AFM1 in raw milk and cheese, and it is the first of its kind in Ethiopia. Determination of AFM1 was conducted using an enzyme-linked immunosorbent assay (ELISA). The results indicated that AFM1 was positive in all samples of milk products. The risk assessment was determined using margin of exposure (MOE), estimated daily intake (EDI), hazard index (HI), and cancer risk. The mean EDIs for raw milk and cheese consumers were 0.70 and 0.16 ng/kg bw/day, respectively. Our results showed that almost all mean MOE values were <10,000, which suggests a potential health issue. The mean HI values obtained were 3.50 and 0.79 for raw milk and cheese consumers, respectively, which indicates adverse health effects for large consumers of raw milk. For milk and cheese consumers, the mean cancer risk was 1.29 × 10−6 and 2.9 × 10−6 cases/100,000 person/year, respectively, which indicates a low risk for cancer. Therefore, a risk assessment of AFM1 in children should be investigated further as they consume more milk than adults.